Cases of Rohingya Refugees in the Perception of International Law - Hidayat, Rifhan Fadhlurrahman (Journal of ASEAN Dynamics and Beyond, 2022)
The issue regarding refugees is now a serious problem for the international community. Human factors and natural factors are the two main causes of refugee-related issues. The Rohingya ethnic group is a case in point of refugees caused by human factors. The Myanmar military junta has imposed pressure on the Rohingya people, while the Government of Myanmar has not recognized the Rohingya people as citizens. This leaves the Rohingya with no citizenship, and thus they are rendered stateless, not receiving any protection from any country. The Rohingya, consequently, flee to other countries to seek asylum. Unfortunately, their presence in a country is, in some cases, forcibly returned by the said country, which is an infringement of the principles of international customary law that civilized countries recognize and abide by. Several laws have been set in place regarding refugee matters, which guarantee the rights of refugees. This includes the right to seek asylum, which is declared in article 14 (1) of the Universal Declaration of Human Rights. However, in many countries, these rights are not respected and refugees are not treated properly. This research aims to analyze the refugee rights of Rohingya asylum seekers under international law. Using a normative legal research approach involving statutory and case approaches, this study will examine the 1951 Convention Relating to the Status of Refugees and its protocols to assess how international law relating to refugee issues can be applied to the Rohingya refugee case. The results of the study will be used to identify how international law can safeguard the rights of Rohingya refugees and point to the responsibilities of countries to provide such protection.